Pembuatan Bubuk Srikaya Instan : Pengaruhnya terhadap Sifat Fisiko-Kimia dan Sensoris - Satrijo Saloko (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
Studies on the production of sugar-apple instant powder (SaIP) and its effects on physicochemical and sensory properties were done. Extracting its fruits to produce sugarapple fruit juice and then freeze dried made SaIP. This research was aimed to have a good quality of SaIP from an addition of sugar of fresh fruit juice and to predict a trend pattern of their physicochemical properties of the product. The results showed that sugar addition gave significantly effect on yield, soluble index, moisture content, total solid, sucrose, vitamin C, total acid, and sensory properties, i.e. colour, flavour and taste. The SaIP preparation with 50% sugar addition was better than other treatment.